Influenza virus hemagglutinin and neuraminidase cytoplasmic tails control particle shape. - Jin, H (1997)
The cytoplasmic tails of the influenza virus glycoproteins hemagglutinin (HA) and neuraminidase (NA) are highly conserved in sequence for all virus subtypes and it is believed that assembly of this enveloped virus depends on interactions of these domains with cytoplasmic viral components. However, it is possible to rescue altered influenza viruses lacking either the HA or NA cytoplasmic tails. We have obtained an influenza virus that lacks both the cytoplasmic tail of HA and NA. Particle production is reduced approximately 10-fold but these particles, although having a fairly normal protein composition, are greatly elongated and of extended irregular shape. We propose a model in which the interactions of the cytoplasmic tails of HA and NA with an internal viral component are so important for spherical virion shape that there is dual redundancy in the interactions.